2015
DOI: 10.1002/jppr.1069
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the peri‐operative period on cognition in older individuals

Abstract: This review aims to highlight the importance of peri-operative and longer-term postoperative cognitive changes and to put them in the context of other cognitive disorders. Cognitive decline is common among the elderly and is impacted by many factors, both known and unknown. Individuals aged 65 years and above comprise the most frequent users of the healthcare system; thus this group is at risk of both cognitive decline associated with ageing, such as mild cognitive impairment and Alzheimer's disease, and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Cognitive reserve and trajectory are perhaps the most important factors that influence the risk of POCD. 29 Additional factors include length and complexity of the surgery (with cardiac surgery possibly being more risky than noncardiac surgery), 20,28 a history of alcohol abuse, 30 previous stroke, 28 diabetes mellitus, hypertension, atherosclerosis, 31 and postoperative complications, especially respiratory complications and postoperative infections. 27 A recent study has also identified gender as a factor, with females being at greater risk than males, 32 as is the case with AD.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Cognitive reserve and trajectory are perhaps the most important factors that influence the risk of POCD. 29 Additional factors include length and complexity of the surgery (with cardiac surgery possibly being more risky than noncardiac surgery), 20,28 a history of alcohol abuse, 30 previous stroke, 28 diabetes mellitus, hypertension, atherosclerosis, 31 and postoperative complications, especially respiratory complications and postoperative infections. 27 A recent study has also identified gender as a factor, with females being at greater risk than males, 32 as is the case with AD.…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Post-operative cognitive dysfunction (POCD) occurs frequently after major surgery [ 1 ]. It is broadly defined as an impairment of a patient’s cognitive functioning relative to their pre-surgery cognitive status [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large individual differences in POCD spanning cognitive recovery during the first few months to persistent cognitive impairment have been reported [1-5]. Although it has been the subject of extensive research during the past two decades, many questions remain unanswered, and a lack of uniform diagnostic criteria [6] and differences in length of follow-up period hamper comparability between studies. Little is currently known about potential risk factors, which help to identify at-risk patients and shed light on underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%